The expression of growth hormone releasing hormone (GHRH) and its receptors in breast carcinomas with apocrine differentiation - further evidence of the presence of a GHRH pathway in these tumors - Kővári Bence; Vranic Semir; Marchio Caterina; Sapino Anna; Cserni Gábor (2017)
Apocrine breast carcinomas were evaluated for the expression of components of the growth hormone-releasing hormone (GHRH) autocrine/paracrine pathway: GHRH and its receptors (GHRH-R), as mammary apocrine carcinomas and epithelium seemed to be uniformly positive for GHRH-R in a pilot study. The apocrine phenotype was determined on the basis of hematoxylin-eosin morphology and a congruent immunohistochemical profile (estrogen receptor negativity, androgen receptor and gross cystic disease fluid protein-15 positivity). Thirty five formalin-fixed paraffin-embedded apocrine breast cancers in tissue microarrays and 24 cases using whole tissue sections were evaluated for GHRH-R and GHRH expression by immunohistochemistry using polyclonal antibodies raised against various domains of GHRH-R and one polyclonal antibody specific for GHRH. GHRH-R positivity was detected in the overwhelming majority (ranging from 90% to 100%) of apocrine breast carcinomas with all but one of the antibodies applied. The expression was usually diffuse with only isolated cases showing positivity in less then 50% of tumor cells. With the PA5-33583 antibody, GHRGH-R positivity was seen only in 73% of the cases in at least 50% of the tumor cells. GHRH expression was also present in all but one cases tested, with more than 50% of the cells expressing it in 30/34 cases. These results support a high rate of GHRH-R and GHRH expression in apocrine breast carcinomas. Whether these findings can be exploited for the targeted treatment of apocrine breast carcinomas with GHRH antagonists requires further study.